Reference values for 75 g oral glucose tolerance test in pregnancy. Issue 6623 (5th March 1988) - Hatem, M; Anthony, F; Hogston, P; Rowe, D J F; Dennis, K J
Abstract : A 75 g oral glucose tolerance test was performed in 212 pregnant women with no predisposing factors suggesting glucose intolerance to establish the normal pattern of glucose metabolism in pregnancy. Reference values for the test were established for the middle of pregnancy (14-20 weeks, n=43) and late pregnancy (28-37 weeks, n=168). One woman was excluded because she had diabetes that required treatment with insulin. There were statistically significant differences between the two groups for samples taken both one and two hours after the glucose load. Reference ranges for the interpretation of the glucose tolerance test in pregnancy should therefore take account of the period of gestation. Arbitrary upper limits of normal (represented by the 97·5 centile) two hours after a 75 g oral glucose load are proposed at 7·5 and 9·6 mmol/l for the second and third trimesters, respectively.